Caring for Individuals With Intellectual and Developmental Disabilities in the COVID-19 Crisis. Issue 2 (April 2021) - Sanders, Jessica Solomon; Keller, Seth; Aravamuthan, Bhooma R.
Abstract : Individuals with intellectual and developmental disabilities (IDDs) are among our most medically vulnerable neurologic patient population. As such, they are at particular risk of psychosocial and medical harm during the coronavirus disease 2019 (COVID-19) pandemic. Here, we highlight strategies to decrease potential infectious exposures and ensure continued optimal neurologic care for individuals with IDD during the COVID-19 pandemic. Finally, in a climate of potential medical resource restriction, we offer some suggestions for advocacy on behalf of individuals with IDD.